2022
DOI: 10.3390/nu14142812
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-Controlled Trial to Test the Effects of a Nutraceutical Combination Monacolin K-Free on the Lipid and Inflammatory Profile of Subjects with Hypercholesterolemia

Abstract: Background: Nutraceutical combinations (NCs) against hypercholesterolemia are increasing in the marketplace. However, the availability of NCs without monacolin K is scarce even though the statin-intolerant population needs it. Methods: This study is a parallel-group, randomized, placebo-controlled, double-blind trial. We evaluated the effects of the NC containing phytosterols, bergamot, olive fruits, and vitamin K2 on lipid profile and inflammatory biomarkers in 118 subjects (mean age ± SD, 57.9 ± 8.8 years; 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The effects of 4-week time-restricted eating (TRE), a popular form of intermittent fasting, determined downregulation of a miRNA panel (miR-4649-5p, miR-2467-3p, miR-543, miR-301a-3p, miR-3132, miR-19a-5p, miR-495-3p, and miR-4761-3p), which, in turn, could inhibit cell growth pathways while activating cell survival and promoting healthy aging (NCT03590847) [ 152 ]. A study conducted on 125 subjects with hypercholesterolemia (ACTRN12619000170123) evaluated the effect of daily assumption of a nutraceutical combination containing 400 mg phytosterols, 100 mg bergamot extract, 20 mg olive extract, and 52 µM vitamin K2 up to 12 weeks of treatment [ 153 ]. The evaluated nutraceutical combination did not change the serum lipid profile and inflammation-related miRNAs and biomarkers [ 153 ].…”
Section: Latest Dietary Mirna-based Animal Models and Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of 4-week time-restricted eating (TRE), a popular form of intermittent fasting, determined downregulation of a miRNA panel (miR-4649-5p, miR-2467-3p, miR-543, miR-301a-3p, miR-3132, miR-19a-5p, miR-495-3p, and miR-4761-3p), which, in turn, could inhibit cell growth pathways while activating cell survival and promoting healthy aging (NCT03590847) [ 152 ]. A study conducted on 125 subjects with hypercholesterolemia (ACTRN12619000170123) evaluated the effect of daily assumption of a nutraceutical combination containing 400 mg phytosterols, 100 mg bergamot extract, 20 mg olive extract, and 52 µM vitamin K2 up to 12 weeks of treatment [ 153 ]. The evaluated nutraceutical combination did not change the serum lipid profile and inflammation-related miRNAs and biomarkers [ 153 ].…”
Section: Latest Dietary Mirna-based Animal Models and Clinical Trialsmentioning
confidence: 99%
“…A study conducted on 125 subjects with hypercholesterolemia (ACTRN12619000170123) evaluated the effect of daily assumption of a nutraceutical combination containing 400 mg phytosterols, 100 mg bergamot extract, 20 mg olive extract, and 52 µM vitamin K2 up to 12 weeks of treatment [ 153 ]. The evaluated nutraceutical combination did not change the serum lipid profile and inflammation-related miRNAs and biomarkers [ 153 ].…”
Section: Latest Dietary Mirna-based Animal Models and Clinical Trialsmentioning
confidence: 99%
“…The same trial demonstrated a decrease in levels of matrix metalloproteinases (MMPs) 2 and 9, which are considered markers of atherosclerotic plaque stability [ 219 ]. Moreover, monacolin K in nutraceutical combination with phytosterols, hydroxytyrosol, and vitamin E confirmed reduction in LDL-C and hsCRP levels in subjects with previously untreated hypercholesterolemia and low or moderate cardiovascular risk [ 220 ], while monacolin K-free combination did not demonstrate analogous results [ 221 ]. Ferulic acid supplementation reduced LDL-C, oxidized LDL-C, hsCRP, and TNF-α, as well as other lipids, oxidative stress, and inflammatory biomarkers in hyperlipidemic subjects [ 222 ].…”
Section: Lipid-lowering Upplementsmentioning
confidence: 99%